2001
DOI: 10.1101/gad.912901
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 recruits the anaphase-promoting complex for ubiquitination and degradation of SnoN

Abstract: Smad proteins mediate transforming growth factor-β (TGF-β) signaling to regulate cell growth and differentiation. SnoN is an important negative regulator of TGF-β signaling that functions to maintain the repressed state of TGF-β target genes in the absence of ligand. On TGF-β stimulation, Smad3 and Smad2 translocate into the nucleus and induce a rapid degradation of SnoN, allowing activation of TGF-β target genes. We show that Smad2- or Smad3-induced degradation of SnoN requires the ubiquitin-dependent proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…We first assessed whether immunoprecipitation with the pan UB nanobody enables the detection of endogenous SKIL ubiquitylation. Although TGF-β-induced SKIL degradation has been well documented ( 4 , 5 , 6 , 29 ), no study has provided evidence of an increased ubiquitylation of SKIL upon TGF-β signaling, presumably because of the difficulty to detect endogenous ubiquitylation and because overexpression experiments temper this inducible effect. We found that immunoprecipitation with the pan UB nanobody enables the detection of increased endogenous SKIL ubiquitylation in the parental U2OS cells after 1 h TGF-β treatment in presence of proteasome inhibitor MG132, but not in the two RNF111-RING-KO clones despite the presence of equivalent amount of SKIL protein in the input of each condition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first assessed whether immunoprecipitation with the pan UB nanobody enables the detection of endogenous SKIL ubiquitylation. Although TGF-β-induced SKIL degradation has been well documented ( 4 , 5 , 6 , 29 ), no study has provided evidence of an increased ubiquitylation of SKIL upon TGF-β signaling, presumably because of the difficulty to detect endogenous ubiquitylation and because overexpression experiments temper this inducible effect. We found that immunoprecipitation with the pan UB nanobody enables the detection of increased endogenous SKIL ubiquitylation in the parental U2OS cells after 1 h TGF-β treatment in presence of proteasome inhibitor MG132, but not in the two RNF111-RING-KO clones despite the presence of equivalent amount of SKIL protein in the input of each condition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mutation of lysine 343 together with the adjacent lysine 342 did not result in attenuated SKIL ubiquitylation. A previous study on overexpressed SKIL lysine mutants has shown that SKIL degradation in response to TGF-β depends on lysine 440, 446, and 449, but no ubiquitylation experiments have confirmed this observation ( 29 ). It is, however, possible that RNF111 ubiquitylates multiple lysines on SKIL including lysine 343, and other lysines such as lysine 440, 446, and 449 that were not detected in the ubiquitylome.…”
Section: Discussionmentioning
confidence: 96%
“…Mutation of a given lysine residue often results in selection of alternative ones. Multiple lysine residues need to be mutated to prevent substrate ubiquitination and degradation ( ). This implies that either multiple lysines are capable of being ubiquitinated or selection of an alternative ubiquitination site when the predominant ubiquitination site was mutated.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant mice were, however, prone to inflammation, which correlated with fewer iTreg cells. The incomplete ablation of iTreg cells could be due to SKI and SnoN degradation by other E3 ligases, such as anaphase-promoting complex ( Stroschein et al, 2001 ; Wan et al, 2001 ) and Smurf2 ( Bonni et al, 2001 ). Alternatively, SKI and SnoN repression of Foxp3 could be compensated by up-regulated transcriptional activators.…”
Section: Resultsmentioning
confidence: 99%